Clinical study at gastroduodenal bleeding and its relationship to secondary hyperparathyroidism in patients on hemodialysis - Nishitani, Hiroshi (Jinko Toseki Kenkyukai kaishi. [Journal of the Dialysis Research Society, 1985)
In order to understand the characteristics of upper gastrointestinal bleeding, which often occurs in patients being treated by hemodialysis, the upper gastrointestinal disorders of 252 patients on hemodialysis were surveyed over a four-year period. Regarding the patients with gastroduodenal bleeding, the clinical features were investigated, especially in order to find if there was a relationship of gastroduodenal bleeding with hypergastrinemia or with secondary hyperparathyroidism. 1) Gastroduodenal bleeding occurred in 11.9% of these subjects. Hemorrhagic gastritis was the most frequent cause of gastroduodenal bleeding (40% of the cases). 2) In the subjects with gastroduodenal bleeding not including ulcers, and especially in those with hemorrhagic gastritis, the onset was frequently associated with abrupt gross hemorrhage (hematemesis or melena); there was difficulty in reaching hemostasis, and large blood transfusions were often necessary. For these reasons, gastroduodenal bleeding not including ulcers was seen to be a clinically important form of gastroduodenal bleeding in patients on hemodialysis. 3) Sex, history of peptic ulcer, seasonal variation, stress, use of drugs, and period of hemodialysis all seemed possible factors of trigger for the gastroduodenal bleeding of the subjects. 4) In this study, hypergastrinemia was not related to gastroduodenal bleeding. The fasting gastrin level of the patients with gastroduodenal bleeding was relatively low, and the frequency of gastroduodenal bleeding in patients with hypergastrinemia was also low. 5) Fasting c-PTH levels of patients with gastroduodenal bleeding were relatively higher than in the patients on hemodialysis as a whole. Frequency of gastroduodenal bleeding was significantly higher in subjects with severe secondary hyperparathyroidism than with the mild form. The frequency of requiring large blood transfusions was higher in patients with both gastroduodenal bleeding and severe secondary hyperparathyroidism. These clinical findings suggest that secondary hyperparathyroidism, especially in its severe form, must be a factor in the gastroduodenal bleeding of patients on hemodialysis. 6) The frequency of requiring large blood transfusions decreased significantly when cimetidine was given to patients with gross hemorrhage. Cimetidine is effective in treating gastroduodenal bleeding in patients on hemodialysis.